Exploring the role of the multiple sclerosis susceptibility gene CLEC16A in T cells. (20th May 2021) - Eriksson, Anna M.; Leikfoss, Ingvild Sørum; Abrahamsen, Greger; Sundvold, Vibeke; Isom, Martine Mesel; Keshari, Pankaj K.; Rognes, Torbjørn; Landsverk, Ole J. B.; Bos, Steffan D.; Harbo, Hanne F.; Spurkland, Anne; Berge, Tone
Abstract: C‐type lectin‐like domain family 16 member A ( CLEC16A ) is associated with autoimmune disorders, including multiple sclerosis (MS), but its functional relevance is not completely understood. CLEC16A is expressed in several immune cells, where it affects autophagic processes and receptor expression. Recently, we reported that the risk genotype of an MS‐associated single nucleotide polymorphism in CLEC16A intron 19 is associated with higher expression of CLEC16A in CD4 + T cells. Here, we show that CLEC16A expression is induced in CD4 + T cells upon T cell activation. By the use of imaging flow cytometry and confocal microscopy, we demonstrate that CLEC16A is located in Rab4a‐positive recycling endosomes in Jurkat TAg T cells. CLEC16A knock‐down in Jurkat cells resulted in lower cell surface expression of the T cell receptor, however, this did not have a major impact on T cell activation response in vitro in Jurkat nor in human, primary CD4 + T cells.